Circ_0075829 facilitates the progression of pancreatic carcinoma by sponging miR‐1287‐5p and activating LAMTOR3 signalling. Issue 24 (13th November 2020) - Zhang, Xudong; Xue, Cailin; Cui, Xiaohan; Zhou, Zhao; Fu, Yue; Yin, Xu; Wu, Siyuan; Gong, Yu; Liu, Yi; Zhu, Chunfu; Qin, Xihu
Abstract: Pancreatic cancer (PC) is a leading cause of cancer‐related mortality globally. Though increasing evidence has demonstrated that circular RNAs (circRNAs) are linked to the development and progression of cancers, the biological functions of circRNAs in PC remain largely unexplored so far. Based on previous studies, Hsc_circ_0075829 (circ_0075829) was screened out and then further identified in PC clinical specimens and cell lines by real‐time PCR. After the stability tests, a series of in vitro and in vivo functional experiments were performed to investigate the role of circ_0075829 in PC development. Furthermore, fluorescent in situ hybridization (FISH), bioinformatics tools, dual‐luciferase assays and rescue experiments were conducted to clarify the regulatory mechanisms of circ_0075829 in SW1990 and BxPC‐3 cells. Compared with paracancerous tissues, the expression of circ_0075829 was increased in PC tissues, which was positively correlated with the clinical features of PC. Knockdown of circ_0075829 significantly suppressed the proliferative, migratory and invasive rates of SW1990 and BxPC‐3 cells both in vitro and in vivo. Bioinformatics analysis and dual‐luciferase reporter gene assay indicated that circ_0075829 could bind to miR‐1287‐5p. Mechanism research and rescue experiments demonstrated that circ_0075829 could regulate the LAMTOR3/p‐ERK signalling pathway via sponging miR‐1287‐5p in PC cell lines. Our data reveal that the circ_0075829 could facilitate the proliferation and metastasis of PC through circ_0075829/miR‐1287‐5p/LAMTOR3 axis.